Characterization of polysaccharide from Lonicera japonica Thunb leaves and its application in nano-emulsion - Li, Yongchao; Liu, Benguo; Yang, Jing; Sun, Junliang; Ran, Junjian; Liang, Xinhong; Li, Yinglin (Frontiers in Nutrition, 2023)
The polysaccharides in honeysuckle leaves (PHL) were separated and characterized for the first time. The nano-emulsion stabilized by PHL and whey protein isolate (WPI) were also fabricated based on the ultrasonic method. The results indicated that PHL was mainly composed of glucose (47.40 mol%), galactose (19.21 mol%) and arabinose (20.21 mol%) with the weight-average molecular weight of 137.97 ± 4.31 kDa. The emulsifier concentration, WPI-to-PHL ratio, ultrasound power and ultrasound time had significant influence on the droplet size of PHL-WPI nano-emulsion. The optimal preparation conditions were determined as following: emulsifier concentration, 1.7%; WPI/PHL ratio, 3:1; ultrasonic power, 700 W; ultrasonic time, 7 min. Under the above conditions, the median diameter of the obtained nano-emulsion was 317.70 ± 5.26 nm, close to the predicted value of 320.20 nm. The protective effect of PHL-WPI emulsion on β-carotene against UV irradiation was superior to that of WPI emulsion. Our results can provide reference for the development of honeysuckle leaves.